Six-month evaluation of ART one-surface restorations in a community with high caries experience in Brazil Avaliação de seis meses de restaurações ART de classe I em uma comunidade de alta experiência de cárie no Brasil - Eduardo Bresciani; Wendell Lima de Carvalho; Lúcia Coelho Garcia Pereira; Terezinha de Jesus Esteves Barata; Franklin García-Godoy; Maria Fidela de Lima Navarro (University of São Paulo, 2005)
The aim of this study to evaluate the success rate in one-surface ART restorations placed in permanent molars using a glass ionomer cement especially developed for ART in a community with high caries experience; to evaluate the operator influence on its success, post-operative sensitivity and technique acceptance by patients. Prior to placement of the restorations, the Gingival Bleeding Index, Visible Plaque Index, DMFT, dmft indices and treatment needed were assessed. One hundred and fifty five one-surface restorations were placed in permanent molars of school children, according to the WHO ART manual, 1997. After 6 months, the success rate was verified clinically and by slides. At baseline, the mean DMFT was 2.56 (±1.08) and the mean dmft, 2.53 (±2.33). Operators A and B have placed 102 and 53 ART restorations respectively. The mean time of placement was 16 minutes and 25 seconds to operator A and 14 minutes and 43 seconds to operator B. At 6-month follow up, 152 ART restorations were evaluated and 97.3% were assessed to be successful. Two restorations were excluded from the sample because the ART restorations were replaced by amalgam fillings. Only 4 restorations have failed, in which 2 due to caries, 1 due to fistula presence and the other because the restoration was lost. Four patients reported postoperative sensitivity. At this study period, ART treatment seems to be suitable for its purpose. Further evaluations are necessary to the new glass ionomer cements especially developed for ART technique provided good results at 6-month follow up in a community with high DMFT and dmft indices. The success rate for one-surface cavities in permanent molars was 97.3%, and the studied indices seemed to have no influence in this early evolution period. O objetivo deste estudo foi avaliar o índice de sucesso de restaurações de cavidade de classe I, realizadas em molares permanentes, utilizando-se a técnica do ART e um cimento de ionômero de vidro desenvolvido especialmente para a técnica, em uma comunidade de alto risco à cárie; avaliar a influência do operador no sucesso da técnica e avaliar a sensibilidade pós-operatória e a aceitação da técnica por parte dos pacientes. Antes da realização do tratamento verificou-se o índice de placa visível e o índice de sangramento gengival, CPOD, ceo-d e necessidade de tratamento. Um total de 155 restaurações de uma superfície foram realizadas em molares permanentes de escolares, de acordo com o manual de ART da OMS. Após 6 meses, realizou-se o acompanhamento clínico e por diapositivos. Inicialmente, o CPOD foi de 2,56 ( ±1,08) e o ceod de 2,53 ( ±2,33 ). Os operadores A e B realizaram 102 e 53 restaurações de ART respectivamente. O tempo médio para o tratamento foi de 16 minutos e 25 segundos para A e 14 minutos e 43 segundos para B. Aos seis meses. 152 restaurações foram avaliadas e 97,3% consideradas sucesso. Duas restaurações foram excluídas da amostra pois foram substituídas por amálgama. Somente 4 restaurações falharam, duas por recidiva de cárie, 1 por presença de fistula e a última por perda da restauração. Quatro pacientes relataram sensibilidade pós-operatória. O tratamento ART cumpriu seus objetivos no período analisado. Avaliações futuras são necessárias, especialmente para os cimentos de ionômero de vidro de alta viscosidade, devido aos bons resultados nesta comunidade de alto índice de cárie. O índice de sucesso foi de 97,3% e os índices de cárie parecem não influenciar no sucesso do tratamento.